(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Background: In recent times, cancer has emerged as a major health concern. It was established that every antagonist of the dihydrofolate reductase exhibits anti-cancer activity. For anti-cancer action, several Schiff-based derivatives with azetidinone rings were designed and docked against the dihydrofolate reductase protein (PDB id:6CXK) in the current work. The ligands were compared to those of standard antagonists of dihydrofolate reductase, that is, trimethoprim and pyrimethamine. Materials and Methods: The ligands were drawn in.mol format using ChemSketch software and converted to.pdb format using Avogadro software. The iGEMDOCK software was utilized to conduct molecular docking investigations, and Discovery Studio Visualizer was ultimately used to visualize the results. Results and Discussion: Most compounds have demonstrated a better affinity for binding to the dihydrofolate reductase. Most of the ligands have demonstrated nearly the same binding affinities as that of the standard dihydrofolate reductase, such as trimethoprim (−102.1 kcal/mol) and pyrimethamine (−91.8 kcal/mol). The top 2 compounds 3A8B (−100.6 kcal/mol) and 3A9B (−94.6 kcal/mol) were chosen for visualization. Conclusion: Schiff base derivatives with azetidinone ring have the potential to be a promising class of drugs for the treatment of anti-cancer action since they have a higher binding affinity to the dihydrofolate reductase than standard antagonists.